Automotive mechanics - Crouse, William Henry; Anglin, Donald L. (New York : Glencoe/McGraw-Hill, 1993)
Automotive service and shop work. Automotive engines. Automotive engine systems. Automotive electrical and electronic equipment. Engine performance and driveability...
Keywords: Automobiles; Mechanics; Automobiles; Automobiles -- Maintenance and repair; Automobiles -- Maintenance and repair -- Examinations, questions, etc